14-3-3ζ is crucial for the conversion of labile short-term object recognition memory into stable long-term memory - Navarro-Lobato, Irene; Masmudi-Martín, Mariam; Quiros-Ortega, María Elena; Gaona-Romero, Celia; Carretero-Rey, Marta; Rey-Blanes, Cristina; Khan, Zafaruddin (John Wiley & Sons, 2021)
The consolidation of new memories into long-lasting memories is multistage process characterized by distinct temporal dynamics. However, our understanding on the initial stage of transformation of labile memory of recent experience into stable memory remains elusive. Here, with the use of rats and mice overexpressing a memory enhancer called regulator of G protein signaling 14 of 414 amino acids (RGS14414) as a tool, we show that the expression of RGS14414 in male rats' perirhinal cortex (PRh), which is a brain area crucial for object recognition memory (ORM), enhanced the ORM to the extent that it caused the conversion of labile short-term ORM (ST-ORM) expected to last for 40 min into stable long-term ORM (LT-ORM) traceable after a delay of 24 hr, and that the temporal window of 40 to 60 min after object exposure not only was key for this conversion but also was the time frame when a surge in 14-3-3ζ p rotein w as o bserved. A k nockdown o f 14-3-3ζ gene abrogated both the increase in 14-3-3ζ protein and the formation of LT-ORM. Furthermore, this 14-3-3ζ upregulation increased brain-derived growth factor (BDNF) levels in the time frame of 60 min and 24 hr and 14-3-3ζ knockdown decreased the BDNF levels, and a deletion of BDNF gene produced loss in mice ability to form LT-ORM. Thus, within 60 min of object exposure, 14-3-3ζ facilitated the conversion of labile ORM into stable ORM, whereas beyond the 60 min, it mediated the consolidation of the stable memory into long-lasting ORM by regulating BDNF signaling.
Keywords: Memoria; Labile memory; Memory consolidation; Memory transformation; RRID:AB_2218378; RRID:AB_2259044; RRID:IMSR_JAX:002266; RRID:RGD_2308816; Stable memory